2022
DOI: 10.3390/axioms11080410
|View full text |Cite
|
Sign up to set email alerts
|

Design of Type-3 Fuzzy Systems and Ensemble Neural Networks for COVID-19 Time Series Prediction Using a Firefly Algorithm

Abstract: In this work, information on COVID-19 confirmed cases is utilized as a dataset to perform time series predictions. We propose the design of ensemble neural networks (ENNs) and type-3 fuzzy inference systems (FISs) for predicting COVID-19 data. The answers for each ENN module are combined using weights provided by the type-3 FIS, in which the ENN is also designed using the firefly algorithm (FA) optimization technique. The proposed method, called ENNT3FL-FA, is applied to the COVID-19 data for confirmed cases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Finally, they suggested a real case study in the United States to validate their problem. Melin et al ( 2022 ) proposed a method called ENNT3FL-FA that combines ensemble neural networks and type-3 fuzzy inference systems to predict COVID-19 data for confirmed cases in 12 countries. The method seeks to find the best possible parameters for each module of the ENN and the type-3 FIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, they suggested a real case study in the United States to validate their problem. Melin et al ( 2022 ) proposed a method called ENNT3FL-FA that combines ensemble neural networks and type-3 fuzzy inference systems to predict COVID-19 data for confirmed cases in 12 countries. The method seeks to find the best possible parameters for each module of the ENN and the type-3 FIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, Luo et al ventured into the realm of the Internet of Vehicles, analyzing, and forecasting macro-scale big data concerning driving behaviors via adaptive fuzzy cyclic neural networks [30]. In the healthcare sector, Melin et al and Castillo et al demonstrated the application of fuzzy systems to predict the trajectory of confirmed COVID-19 cases, providing crucial insights for pandemic management [31,32]. Collectively, these studies underscore the versatility and robustness of FNNs as a tool for tackling diverse predictive challenges characterized by fuzziness and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Improved performance of interval type-3 and general type-2 systems over type-1 fuzzy systems has been illustrated in diverse settings, including industrial applications, e.g., flowmeter fault reporting, product temperature prediction and battery management [12]- [16], and financial and health applications requiring time series predictions [17], [18]. Higher-order fuzzy sets have also been employed to represent group or consensus decisions (e.g., [19]- [21]).…”
Section: Introductionmentioning
confidence: 99%